1996
DOI: 10.1007/bf00731474
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside composition of the rat choriocarcinoma cell line, Rcho-1

Abstract: The Rcho-1 cell line, originally established from a rat choriocarcinoma, shows differentiation into placental trophoblastic giant cell-like cells and has been used to study the mechanism of placental function control. In the present study, we analysed the ganglioside composition of Rcho-1 cells by HPTLC orcinol/H2So4, TLC/ immunostaining and immunohistochemistry. Rcho-1 cells expressed GM3 and GD3 as the major gangliosides and CTH as major neutral glycolipid when they were cultured in growth medium (20% FCS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In a previous study, we found that Rcho-1 cells, which were originally established from a rat choriocarcinoma [29,30] and differentiate into placental trophoblastic giant cell-like cells [30][31][32], expressed GM3 and GD3 as the major gangliosides depending on the culture conditions [33]. The composition of glycolipids is conserved in Rcho-1 cells and is very similar to that in the rat placenta.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study, we found that Rcho-1 cells, which were originally established from a rat choriocarcinoma [29,30] and differentiate into placental trophoblastic giant cell-like cells [30][31][32], expressed GM3 and GD3 as the major gangliosides depending on the culture conditions [33]. The composition of glycolipids is conserved in Rcho-1 cells and is very similar to that in the rat placenta.…”
Section: Discussionmentioning
confidence: 93%